Permanent Spacers Are a Reliable Solution for Peri-prosthetic Shoulder Infection: A Systematic Review. Issue 3 (October 2020) - Alessio-Mazzola, Mattia; Repetto, Ilaria; Russo, Antonio; Clemente, Antonio; Ventura, Niccolò; Formica, Matteo; Burastero, Giorgio; Felli, Lamberto
Background: Peri-prosthetic shoulder infection (PSI), a highly disabling complication of shoulder arthroplasty, often requires additional surgery and prolonged antibiotic therapy. Of strategies proposed to manage this devastating condition, the use of cement spacers, perhaps even as a definitive treatment, is debated. Questions/Purposes: We sought to systematically review the literature on antibiotic-loaded cement spacers as a viable, perhaps definitive, treatment for PSI, evaluating the eradication rates, mechanical reliability, and functional results related to its use. Methods: We conducted a systematic review of studies published from January 1, 1980, through September 1, 2019. Following the Cochrane Handbook of Systematic Reviews of Interventions and Preferred Reporting Items for Systematic Review and Meta-analysis, we searched for studies reporting functional and clinical outcomes in patients with PSI treated with a permanent spacer of the shoulder. Two independent reviewers searched eight databases, as well as reference lists of the retrieved articles. Results: After exclusion criteria were applied, 12 studies were included, involving a total of 143 patients. The mean age was 65.8 years; the mean follow-up was 37.4 months. A total of 133 patients (93%) were free from infection at latest follow-up. The mean post-operative active elevation of the shoulder ranged from 48.6 to 90°, the mean abduction ranged from 51 to 75°, and external rotation ranged from 3.6 to 29°. The mean Constant–Murley score ranged from 20.6 to 42 points (out of 100, from worst to best). Conclusion: The use of a permanent cement spacer is a reliable solution to PSI in low-demand, older patients with comorbidities, a population in whom it is desirable to avoid additional surgery. Our review found a high rate of infection eradication and moderate-to-good objective and subjective results. However, the overall level of evidence of included studies was very low, and higher-quality studies are needed to clarify the role of permanent spacers in the treatment of PSI.